A Tissue Culture Technique for Rapid Clonal Propagation, Microrhizome Induction, and RAPD Analysis of Kaempferia grandifolia Saensouk & Jenjittikul—A Rare Plant Species in Thailand - Sukanya Nonthalee; Surapon Saensouk; Suthira Maneechai; Phetlasy Souladeth; Piyaporn Saensouk (Horticulturae)
Kaempferia grandifolia Saensouk & Jenjittikul (Zingiberaceae), a rare plant species in Thailand, is commonly used as a medicinal plant, while the young leaves are cooked and eaten as a vegetable. This study focused on the in vitro propagation of K. grandifolia plants to induce the development of shoots, roots, microrhizomes, and acclimatization. The genetic variations between plants grown under in vitro propagation and plants grown in nature were also assessed. An efficient protocol was developed for in vitro propagation of K. grandifolia using microshoots (0.5 cm in length). The optimal responses for shoot multiplication (4.78 ± 1.15 shoots/explant) and root induction (11.56 ± 1.39 roots/explant) were obtained within 8 weeks in Murashige and Skoog (MS) medium supplemented with 3 mg/L of 6-benzylamino purine (BAP) plus 0.5 mg/L of NAA. Microrhizome induction was 80% when the shoot buds were cultured on MS medium supplemented with 2 mg/L of BAP, 1 mg/L of NAA, 11 µM of silver nitrate (AgNO3), and 70 g/L of sucrose after 20 weeks. The survival rate of plantlets was 100% when transplanted to soil and sand. Micropropagated and field-grown donor plants of K. grandifolia showed 91.49% genetic similarity through RAPD analysis.